Comparative study of two incentive schemes in Malaysian paddy production - Yunus-Junaid, Busayo Rashidat; Ismail, Mohd Mansor; Mohd Nawi, Nolila (IDOSI Publications, 2013)
Domestic paddy production has occupied the minds of policy makers since independent. This explains the reason for the formation of granary areas where irrigation schemes enhance productivity of paddy farming. Modern infrastructures and technologies were to increase the self sufficiency and food security levels but unfortunately the country still depends on cheaper rice abroad. The paper analyzed the comparative advantage of paddy production in selected granary areas and examined the government incentive schemes before and after 2008. Two indicators of comparative advantage (Domestic Resource Costs (DRC) and Social Cost-Benefit ratio (SCB)) were used to calculate the comparative advantage of paddy production. The results showed that the new incentive scheme allocates inputs in paddy production more efficiently even in times of global food crisis.